Physical Development of Children of Turkish Origin from the Region of Kardjali in Bulgaria - Nikolova, Mima; Petrov, Ivan (Anthropological Review, 1987)
Examinations were carried out in 500 boys and 500 girls of Turkish origin in the age of 10-14 years living in the region of Kardjali in the southern part of Bulgaria.’ Twenty-five cephalo- and somatometric traits were investigated. The rate of changes taking place in the traits during the development and sexual dimorphism were evaluated and the Turkish children were compared with their pars from Plovdiv. It was found that the children of Turkish origin had lower values of the, investigated traits than the children from Plovdiv. The results are presented in tables 1-3 and in drawings.